Identifying Factors Affecting the Number of Singapore Tourists’ Arrivals to Malaysia using Regression Analysis - Mohd Fadzil, Nur Farah Aliyah; Mohd Salleh, Rohayu (Enhanced Knowledge in Sciences and Technology, 2026)
Tourism has played an important role in Malaysia’s economic development in term of providing to employment, foreign exchange earnings, and the development of related industries. Malaysia's diverse attractions, cultural heritage, and strategic location make it a popular destination for international tourists, particularly those from Singapore. Tourism also benefits local communities by encouraging investment in infrastructure and services. However, the number of Singapore tourist arrival has been inconsistent in some years like in year 2019 until 2022 highlight the need to understand the key factors influencing Singaporean travel patterns. This study used quarterly data from 2010 to 2024. This study examines the factors influencing Singapore tourist arrivals and their long-term relationships. Correlation analysis, Multiple Linear Regression (MLR) and Autoregressive Distributed Lag (ARDL) method were used. The correlation analysis shows that exchange rate, GDP, hotel availability, internet penetration rate, crime rate, number of events and tourist receipts are significantly associated with number of Singapore tourist arrival while inflation rate shows insignificant relationship. From MLR analysis, it has been revealed that GDP, availability of hotels and receipts from tourists are significant factors to the total tourist arrivals. 81.10% of the changes in number of Singapore tourist arrival are explained by the independent variables. From long-run analysis by Autoregressive Distributed Lag (ARDL), it has been revealed that GDP, hotel availability and tourist receipts influence positively in the long run.